The Platelet–Lymphocyte Ratio Associated with Depression in Diabetes Patients in the US National Health and Nutrition Examination Survey - Zhou D (Dove Medical Press, 2021)
Depu Zhou, Jie Wang, Xiaokun Li Department of Endocrinology, Yanbian University Hospital, Yanji City, Jilin Province, People’s Republic of ChinaCorrespondence: Xiaokun Li Email professerlxk@tom.comBackground: This study investigated patients with diabetes mellitus (DM) and the role of the platelet–lymphocyte ratio (PLR) in comorbid clinically relevant depression (CRD) in these individuals, so as to determine the association between PLR and depression.Material and Methods: All data used in this research is originally from the United States National Health and Nutrition Examination Survey (NHANES). CRD in DM patients was screened via a Patient Health Questionnaire-9 (PHQ-9). PLR was calculated by platelet and lymphocyte counts. The associations between PLR and CRD in DM patients were determined using multivariable logistic regression models, weighted generalized additive models, and receiver operating characteristic curve (ROC). The second outcome was the relationship between suicide tendency and PLR.Results: We selected 3537 DM patients from 2009 to 2016 in database. PLR was statistically significantly associated with risk of CRD in diabetic patients (p trend< 0.05 in non-adjusted and adjusted model) and had a predictive value (AUC = 0.559). We also found a U-shaped association between PLR and CRD in patients with DM. The break point was 69.2. To the right of 69.2, the OR (95% CI) was 1.00 (1.00, 1.01). To the left of it, the OR (95% CI) was 0.97 (0.95, 1.00). We have found that PLR is not related to suicidal tendencies.Conclusion: PLR is an independent risk factor for CRD in DM patients, and the relationship between them is nonlinear. When PLR was around 69.2, patients with diabetes had the lowest risk of depression. Further research is needed to clarify the nonlinear relationship between PLR and depression in DM patients.Keywords: diabetes mellitus, the platelet–lymphocyte ratio, depression, NHANES